Mapping the cancer-specific EORTC QLQ-BR53 onto the preference-based EQ-5D-5L instrument: A cross-sectional study in breast cancer in Vietnam - Thuy, Nguyen Thi Thu; Nghi, To Hue; Nhi, Vo Ngoc Yen; Anh, Le Tuan; Ha, Tran Nguyen; Phuong, Pham Thi Cam (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Introduction: The EQ-5D instrument is highly recommended for health economic evaluations but is considered less practical than the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC) QLQ-BR53 in clinical studies with cancer patients. In these cases, cross-walking is recommended to convert the cancer-specific instrument onto the preference-based measures. This study aimed to develop an algorithm for direct mapping the QLQ-BR53 onto the EQ-5D-5L utility index in breast cancer patients. Methods: A cross-sectional study was conducted among patients diagnosed with HER2 breast cancer across six oncology hospitals in Vietnam from July to December 2020. Participants’ health-related quality of life was assessed using QLQ-BR53 and EQ-5D. Two mapping algorithms - ordinary least squares (OLS) and generalized linear regression (GLM) - were compared. The best-fit model was selected based on MAE, RMSE, MAPE, and AIC. Internal validation was done using hold-out and cross-validation methods. Results: The study involved 338 participants with a mean age of 53.87 ± 9.97 years. Most were diagnosed early (55.7%) and non-metastatic (76.6%). The mean EQ-5D utility value was 0.863 ± 0.142. The OLS model was the best fit for mapping EQ-5D utility scores from QLQ-BR53, with goodness-of-fit statistics: MAE = 0.786; RMSE = 0.1038; MAPE = 11.68%; and AIC = -524.2398. Key components included global health status, future perspective, pain, and arm symptoms. Conclusion: The developed model allows mapping QLQ-BR53 breast cancer data to EQ-5D-5L utility values, aiding in calculating quality-adjusted life years (QALYs) for cost-utility analyses in breast cancer.